Effect of supplementation of concentrate mixture or barley grain to grazing goats on nutrient utilization during summer at semiarid region - BHADAURIA, K K S; PAILAN, G H; KUNDU, S S; DAS, M M; LODHI, G N; VERMA, N C (The Indian Journal of Animal Sciences, 2014)
Thirty local female goats available in Bundelkhand region grazed under 2 paddocks @ 1.0 ACU/ha (paddock A) and 2.0 ACU/ha (paddock A) and 2.0 ACU/ha (paddock B) in a shrub omfested grass;amd were se;ected. To nullify the effect of stocking rates half of the goats from each paddock were spplemented with crushed barley grain (group 1) and remaining animals were supplemented concertrate mixture (group 2) during April to July. The goats under both the paddocks primarily selected 6 species ofÂ shrun and less (3.42-7.76% of total forages) quantity of grasses. Digestibility of nutrients was similar in both the grops. N intake/kg DOM intake ws higher (P